Temperature-sensitive dual-segment polarization maintaining fiber Sagnac loop mirror - Lim, Kok Sing; Pua, Chang Hong; Harun, Sulaiman Wadi; Ahmad, Harith (Elsevier, 2010)
A new temperature-sensitive fiber Sagnac loop mirror (FLM) is proposed using two segments of polarization maintaining fiber (PMF). The proposed dual-segment FLM provides greater temperature sensitivity in the spectral spacing detuning compared to the conventional single-segment configuration. Besides, the proposed configuration also enables both efficient positive and negative spectral spacing detuning by rising the temperature of one of the PMF segments. The experimental results show that the proposed configuration has achieved a great improvement in increasing spectral spacing variation range by 6.6 times and an increment of temperature sensitivity as much as 337.6% as compared to the conventional configuration.